Losing Joe's place - Korman, Gordon (New York : Scholastic Inc., 1990)
Jason and his two friends move into Jason's brother's apartment and manage to wreak havoc in it during one funny and memorable summer.
G5
Keywords: Apartment houses -- Fiction; Humorous stories